Peran Suami dalam Pendampingan Kehamilan Istri: Studi Kualitatif pada Masyarakat Kotabaru, Kalimantan Selatan - Yeuis Diah Sri Lestari; Arlin Adam; Andi Alim (Pusat riset dan Inovasi Nasional, 2025)
Pregnancy is a critical phase in a woman's life that demands comprehensive support from her closest environment, especially from her husband. This study aims to describe the role of husbands in accompanying their wives during pregnancy, identify factors that influence the level of involvement, and understand the impact on the physical and psychological health of pregnant women. The research approach used was qualitative with the type of phenomenological study, which was conducted in Kotabaru District, South Kalimantan. The main informants consisted of purposively selected pregnant women and postpartum mothers, complemented by triangulation from husbands, health workers, and community leaders. Data were collected through in-depth interviews, non-participatory observation, and documentation, and analyzed thematically. The results showed that husbands' assistance included involvement in pregnancy check-ups, assistance with household chores, provision of financial and emotional support, and roles in preparing for childbirth. However, this involvement was influenced by the husband's knowledge, culture, communication, and working conditions. Intact support from husbands was shown to have a positive impact on pregnant women's sense of comfort, confidence, mental readiness, and physical health. This study emphasizes the importance of holistic involvement of husbands in the pregnancy process and the need for a family and culture-based approach in preparing for childbirth.